2012
DOI: 10.1111/j.1551-6709.2012.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Offline Improvement in Learning to Read a Novel Orthography Depends on Direct Letter Instruction

Abstract: Improvement in performance after the end of the training session, termed ''Offline improvement,'' has been shown in procedural learning tasks. We examined whether Offline improvement in learning a novel orthography depends on the type of reading instruction. Forty-eight adults received multisession training in reading nonsense words, written in an artificial script. Participants were trained in one of three conditions: alphabetical words preceded by direct letter instruction (LetterAlph); alphabetical words wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…On the one hand, brain research has shown that letter formation facilitates letter perception in words and thus reading words, both in young children [2224,35] and adults [11,23,33,34]. Instructional research has also demonstrated that letter formation in English and character formation in Chinese, can transfer to improved word reading [7,10,57], presumably because perception of letter or character in word context is facilitated by formation of them in handwriting.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, brain research has shown that letter formation facilitates letter perception in words and thus reading words, both in young children [2224,35] and adults [11,23,33,34]. Instructional research has also demonstrated that letter formation in English and character formation in Chinese, can transfer to improved word reading [7,10,57], presumably because perception of letter or character in word context is facilitated by formation of them in handwriting.…”
Section: Introductionmentioning
confidence: 99%
“…The first studies showed that explicit teaching of print-to-sound correspondences facilitates novel word reading in the unfamiliar script (e.g., Bishop, 1964, in adults;Jeffrey & Samuels, 1967, in children), thus supporting the phonic method. Follow-up studies were mostly run in adults (who could be extensively trained and who were quickly able to use a completely new alphabet) and largely confirmed the first results (e.g., Baron & Hodge, 1978;Bitan & Booth, 2012;Bitan & Karni, 2003Bitan, Manor, Morocz, & Karni, 2005;Brooks, 1977Brooks, , 1978Yoncheva, Wise, & McCandliss, 2015). In the same line, artificial characters were used to examine the impact of letter sound or letter name knowledge (e.g., Chisholm & Knafle, 1975;Jenkins, Bausell & Jenkins, 1972;Samuels, 1972) and phonetic feature knowledge (e.g., Byrne, 1984;Byrne & Carroll, 1989) on reading acquisition.…”
Section: Using Unknown and Artificial Characters: State Of The Artmentioning
confidence: 56%
“…At the highest level, prior knowledge may take the form of general linguistic or meta-linguistic knowledge. Support for the role of this type of prior knowledge comes from research showing that individual differences in phonological awareness, vocabulary, and reading skill are predictive of both general word learning success and, more specifically, the time course of novel word consolidation (e.g., Ben-Zion et al, 2019;Bitan & Booth, 2012;James et al, 2019;Landi et al, 2018).…”
Section: The Role Of Prior Knowledge In Novel Word Learningmentioning
confidence: 99%